2019
DOI: 10.1111/1750-3841.14751
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Lutein in Nanoemulsions Stabilized by Resveratrol and Maillard Conjugates

Abstract: Lutein is incorporated into foods as a natural yellow pigment and nutraceutical. The introduction of lutein into many foods and beverages, however, is problematic because of its strong hydrophobicity and poor chemical stability. In this research, lutein‐loaded nanoemulsions were prepared to overcome this problem. Casein‐dextran Maillard conjugates or physical complexes were utilized as emulsifiers, while either medium chain triglycerides (MCT) or grape seed oil (GSO) were used as carrier oils. The impact of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…After 5 days of incubation at 25 °C, samples were centrifuged at 10,000× g (Beckman Instruments) for 15 min and the supernatant (0.05 mL) was diluted in 3.95 mL of DMSO. The unbound resveratrol was quantified by measuring the solution absorbance at 309 using a UV/vis model DU-530 spectrophotometer (Beckman Instruments) [ 21 ]. A solution of bovine casein or caprine casein in DMSO without resveratrol was used as a blank.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 5 days of incubation at 25 °C, samples were centrifuged at 10,000× g (Beckman Instruments) for 15 min and the supernatant (0.05 mL) was diluted in 3.95 mL of DMSO. The unbound resveratrol was quantified by measuring the solution absorbance at 309 using a UV/vis model DU-530 spectrophotometer (Beckman Instruments) [ 21 ]. A solution of bovine casein or caprine casein in DMSO without resveratrol was used as a blank.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the ability of the bovine and caprine caseins to bind resveratrol, mixtures of the casein solutions (2% w/w) dissolved in 5 mM phosphate buffer (pH 7.0) solution and resveratrol dissolved in ethanol (1.25% v/v), at a concentration of 500 µg/mL in the final mixture, were mixed using a magnetic stirrer at low speed for 30 min at 25 • C. The samples were then vortexed and incubated for 5 days at 25 • C. After 5 days of incubation at 25 • C, samples were centrifuged at 10,000× g (Beckman Instruments) for 15 min and the supernatant (0.05 mL) was diluted in 3.95 mL of DMSO. The unbound resveratrol was quantified by measuring the solution absorbance at 309 using a UV/vis model DU-530 spectrophotometer (Beckman Instruments) [21]. A solution of bovine casein or caprine casein in DMSO without resveratrol was used as a blank.…”
Section: Resveratrol Binding To Bovine and Caprine Caseins In Solutionmentioning
confidence: 99%
“…Some other studies have also reported the development of carotenoid based NEs [ 82 , 83 , 84 ]. Comparatively, NEs are among the nanocarotenoid carriers most frequently used in pharmaceutical, food and chemical industries.…”
Section: Preparation Physicochemical Characterization Stability Evaluation and Biological Activitymentioning
confidence: 99%
“…In recent studies, several solutions have been proposed and these methods include lipid nanocarriers or liposomes, nanoemulsions, nanocrystals, etc. These methods do contribute to the solubility of resveratrol [14][15][16][17]. However, it is undeniable that nanomaterials or liposomes have disadvantages, such as difficult and unstable preparation, and excipients (i.e., ethanol and propylene glycol) which are known to have recognized actions or effects are usually used in the preparation [18].…”
Section: Introductionmentioning
confidence: 99%